Analisis Proses Distribusi Pupuk Melalui Angkutan Laut oleh PT Pupuk Indonesia Logistik Jakarta - Sahudiyono Sahudiyono; Sudaryanti Parta (Majalah Ilmiah Bahari Jogja, 2023)
This article aims to describe the fertilizer distribution process at PT Pupuk Indonesia Logistik (PT Pilog). With a descriptive-qualitative method, data were obtained by observation, documentation, and interview. The researcher interviewed two top leaders: the director of administration and finance and the director of operations, and two people at the middle level: the marketing manager and the ship management manager with two staffs. The results of the study were: 1) fertilizer as a commodity whose distribution became the monopoly of PT Pupuk Indonesia Logistik as a part of the Pupuk Indonesia Holding Company (PIHC Group). 2) the distribution pattern of fertilizer followed the policy of the relevant ministry by determining seven sea and land transportation routes according to the type of fertilizer covering all regions of Indonesia. 3) fertilizer distribution services PT. Pilog consisted of three types, namely: Port to Port Service (PTPS), from loading port to unloading destination port, Port to Door Service (PTDS), service from loading port to Line III Warehouse and Door to Door Service (DTDS), services from the factory (producer) to the place of consumers. 4) each mode of sea transportation was responsible for cargo commodities including: dry bulk, general cargo, cargo in bags, liquid gas carriers, project cargo, and other cargo with a fleet of ships belonging to PT. Pilog namely 7 Units of Bulk Carrier Vessels and 2 Units of Ammonia Vessels.